2021
DOI: 10.1159/000516498
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanism of Human Recombinant Leptin-Induced VEGF A Synthesis via PI3K/Akt/mTOR/S6 Kinase Signaling Pathway while Inducing Angiogenesis: An Analysis Using Chicken Chorioallantoic Membrane Model

Abstract: <b><i>Introduction:</i></b> The present study aimed to realize human recombinant leptin ’s ability to synthesize VEGF A while inducing neovascularization through PI3K/Akt/mTOR/S6 kinase involved signaling pathway. <b><i>Methods:</i></b> To examine the PI3K/Akt/mTOR/S6 kinase pathway involvement in leptin-induced VEGF A synthesis, the chick chorioallantoic membrane (CAM) was incubated with human recombinant leptin and specific inhibitors of the proposed signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Various ndings prompted that human recombinant leptin may serve as a regulatory factor for angiogenesis [3,4]. NO plays a critical role in angiogenesis and enhances multiple processes in ECs such as cell survival, proliferation, migration [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various ndings prompted that human recombinant leptin may serve as a regulatory factor for angiogenesis [3,4]. NO plays a critical role in angiogenesis and enhances multiple processes in ECs such as cell survival, proliferation, migration [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…It also acts as a pro-angiogenic molecule and initiates the process of angiogenesis through the Ob-R receptor present on vascular endothelial cells (ECs) [2]. In our previous experiments we speculated that the human recombinant leptin could induce concentration and time dependent angiogenic potential and able to enhance the mRNA transcription level of Vascular Endothelial Growth Factor A (VEGF A) via PI3K/Akt/mTOR/s6Kinase signaling pathway on chick embryo vascular bed [3,4]. Leptin-induced NO releases from eNOS in ECs through the activation of various canonical signaling pathway is considered as one of the critical events in angiogenesis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that Endothelial cells (ECs) express OB-R leptin receptors and the binding of leptin to OB-R enables the growth of small blood vessels [3]. Recently, it has been identified that leptin could induce PI3K/Akt/ mTOR/s6Kinase signaling pathway and enhance VEGF mRNA's transcription level while inducing angiogenesis [4]. One of the intriguing possibilities of leptin is that it promotes neovascularization through paracrine mode concerning the volume of fat mass [25].…”
Section: Inhibits Insulin Secretion and Maintains Bloodglucose Level Leptin Induces Sprouting Of New Vessels From Existing Ones And Enhanmentioning
confidence: 99%
“…It circulates through the bloodstream, engages with normal metabolism, regulates energetic homeostasis, reproductive system, and influences the circadian cycle, lipid inflammation, and carbohydrate mechanisms. Leptin is well known for its pro-angiogenic potential and operates multiple signaling agencies through the receptor located in endothelial cells [3,4]. Leptin is also secrets by other organs, such as the placenta, bone marrow, ovaries, stomach, and cellular structures, including mammary epithelial cells, P/D1 cells, and gastric chief cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin induces an increase in vascular permeability and potentiates VEGF-mediated angiogenesis dose-dependently [ 25 ]. Indeed, leptin induces the synthesis of VEGF-A by endothelial cells, and thus the growth of new blood vessels, via the activation of the PI3K/Akt/mTOR/S6 kinase signaling pathway [ 26 ].…”
Section: Introductionmentioning
confidence: 99%